Search Behavior For Millennial Generation Information - Majidah, Majidah; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2021)
The purpose of this study was conducted to determine the behavior of millennial generation before, during and after searching for information. This research uses descriptive research with a quantitative approach and data collection methods using a questionnaire. The population in this study is the Open University library science students aged 20-24 years, who take tuton classes in the 2019.1 period. Samples were taken using the Slovin formula, so that a sample of 100 people was obtained. The questionnaire was distributed to online students through the Open Universits elearning page. The sample used in this study is accidental sampling in which the researcher chooses a sample from anyone who meets the criteria as a population. This research uses Ellis theory, in which the theory the researcher divides into 3 stages, namely before, during and after searching for information. The results showed that the behavior of Online Class Library Science Students after searching for information was positive, with a score of 3.09, this score was on an interval scale of 2.52 - 3.27. Behavior of Online Class Library Science Students when searching for information is positive, with a score of 3.08, this score is on an interval scale of 2.52 - 3.27. While the Online Class Library Science Student Behavior after searching for information is very positive, with a score of 3.30, this score is on an interval scale of 3.28 - 4.03. Based on the results of the study, the information seeking behavior of Online Class Library Science Students as a whole includes aspects before, during and after searching for information is positive, with a score of 3.16, this score is on an interval scale of 2.52 - 3.27